Correction for particle loss in a regulatory aviation nvPM emissions system using measured particle size. (March 2023) - Durand, Eliot; Durdina, Lukas; Smallwood, Greg; Johnson, Mark; Spirig, Curdin; Edebeli, Jacinta; Roth, Manuel; Brem, Benjamin; Sevcenco, Yura; Crayford, Andrew
Abstract: To reduce the adverse impact of civil aviation on local air quality and human health, a new international standard for non-volatile Particulate Matter (nvPM) number and mass emissions was recently adopted. A system loss correction method, which accounts for the significant size-dependent particle loss, is also detailed to predict nvPM emissions representative of those at engine exit for emissions inventory purposes. As Particle-Size-Distribution (PSD) measurement is currently not prescribed, the existing loss correction method uses the nvPM number and mass measurements along with several assumptions to predict a PSD, resulting in significant uncertainty. Three new system loss correction methodologies using measured PSD were developed and compared with the existing regulatory method using certification-like nvPM data reported by the Swiss and European nvPM reference systems for thirty-two civil turbofan engines representative of the current fleet. Additionally, the PSD statistics of three sizing instruments typically used in these systems (SMPS, DMS500 and EEPS) were compared on a generic aero-engine combustor rig. General agreement between the three new PSD loss correction methods was observed, with both nvPM number- and mass-based system loss correction factors (kSL_num and kSL_mass ) within ±10% reported across the engines tested. By comparison, the existing regulatory method was seen to underpredict kSL_num by up to 67% and overpredict kSL_mass by up to 49% when compared with the measured-PSD-based methods, typically driven by low nvPM mass concentrations and small particle size. In terms of the particle sizing instrument inter-comparison, an agreement of ±2 nm for the GMD and ±0.08 for the GSD was observed across a range of particle sizes on the combustor rig. However, it was seen that these differences can result in a 19% bias for kSL_num and 8% for kSL_mass for the measured-PSD-based methods, highlighting the need for further work towards the standardisation of PSD measurement for regulatory purposes. Highlights: Prediction of real-world aircraft emissions using regulatory nvPM concentrations. System loss correction using measured particle size verified on 32 aircraft engines. Measured-size-based corrections improve regulatory correction for <25 nm & 10 μg/m 3 . nvPM loss correction factors up to 7.8 for number and 2.5 for mass predicted. DMS500, SMPS and EEPS particle size measurements agreed within ±5% for GMD and GSD.